2019
DOI: 10.1111/josl.12343
|View full text |Cite
|
Sign up to set email alerts
|

Discursive shifts associated with coming out: A corpus‐based analysis of news reports about Ricky Martin

Abstract: This study seeks to shed light on the discursive effects of a public sexual identity declaration as they surface in the language used to construct the social actor in question. Subscribing to queer linguistically informed critical discourse studies, it builds on and advances the theoretical discussion of coming out in language and sexuality studies. The investigation analyses a corpus of news reports about Ricky Martin, comparing two sub‐corpora, one with texts published before and another with texts from afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Unlike 'feminist CDA', which uses the framework to problematise patriarchy, sexism, and the gender binary (Lazar 2005), and despite a number of studies using CDA to enable queer linguistic research (e.g. Peterson 2010, Motschenbacher 2019, the naming of this approach as 'queer CDA' is not yet common (though see Jones and Mills 2014). Here, our aim is to reveal the heteronormative biases evident in our corpus of newspaper articles by actively identifying linguistic constructions which frame PrEP negatively due to an association made with gay men.…”
Section: Queer Critical Discourse Studiesmentioning
confidence: 99%
“…Unlike 'feminist CDA', which uses the framework to problematise patriarchy, sexism, and the gender binary (Lazar 2005), and despite a number of studies using CDA to enable queer linguistic research (e.g. Peterson 2010, Motschenbacher 2019, the naming of this approach as 'queer CDA' is not yet common (though see Jones and Mills 2014). Here, our aim is to reveal the heteronormative biases evident in our corpus of newspaper articles by actively identifying linguistic constructions which frame PrEP negatively due to an association made with gay men.…”
Section: Queer Critical Discourse Studiesmentioning
confidence: 99%
“…The analysis concentrates on the usage patterns of the terms gay and homosexual in the Ricky Martin news text corpus. The selection of these terms is motivated by the findings of an earlier, quantitative corpus linguistic study on the same dataset (Motschenbacher 2019), which showed that the semantic domain of sexual identity is strongly overlexicalised in AFTER when compared to BEFORE, where no forms from this semantic domain turn out to be (statistically based) keywords. The two terms from this semantic domain with the highest keyness rankings in AFTER are gay (ranking second) and homosexual (ranking twentieth) are subjected to an in-depth qualitative analysis that concentrates on the inspection of concordance lines (but see Motschenbacher 2019 for an analysis of full texts from the dataset).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Of the sexual identity labels that turn out key in AFTER (Motschenbacher 2019), the relatively value-neutral term gay is clearly most common, with 479 occurrences in AFTER, while the semantically more negative form homosexual* occurs 94 times. On first glance, this leaves the impression of a fairly acceptable representation of same-sex sexualities overall in the more recent corpus.…”
Section: Usage Patterns Of Gay and Homosexual In The Ricky Martin Cormentioning
confidence: 99%
“…For example, research explored and critically reflected on LGBTQ+ individuals' coming out negotiation to family, friends, work colleagues, and strangers via Facebook, YouTube, Twitter, blogs, and online dating platforms (e.g., Chester et al., 2016; Duguay, 2016; Etengoff & Daiute, 2015; George, 2011; Onanuga, 2021; Owens, 2017; Phua, 2020; Steinfeld, 2020; Thompson & Figueroa, 2020; Waggoner, 2022) or on reality TV shows (e.g., Bannink & Wentink, 2015; Boross & Reijnders, 2015, 2017). The analysis of celebrities' coming out and related press coverage has been also of interest (e.g., Benozzo, 2013; Motschenbacher, 2019; Schallhorn & Hempel, 2017; Tinker, 2021). Research further investigated the role of the internet for LGBTQ+ individuals' coming out process (e.g., Bond et al., 2009; Craig & McInroy, 2014; Szulc & Dhoest, 2013).…”
Section: Three‐lens Typologymentioning
confidence: 99%